Peran Mediasi Organizational Commitment pada Pengaruh Job Satisfaction terhadap Turnover Intention pada Karyawan PT Pancaputra Mitratama Mandiri - Gita Kusuma Dewi; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
PT Pancapaputra Mitratama Mandiri is an authorized lubricant distributor of PT Shell Indonesia. The company was founded in 2004. The company is a distributor office of Shell Lubricants products for the industrial and transportation scope in the East Java Region. This research purposes to test and explain the impact of job satisfaction on turnover intention through organizational commitment as a mediator variable at PT Pancaputra Mitratama Mandiri. The approach adopted in this study is quantitative, while the sampling technique in this study is saturated sample with the number of all employees of PT Pancaputra Mitratama Mandiri as respondents who were taken part as many as 32 employees. Data on this research were analyzed making use of Partial Least Square (PLS) with the assistance of SmartPLS 3.0. software on the computer. The outcomes further revealed a significant negative relationship between Job Satisfaction and Organizational Commitment on Turnover Intention. The results provide a conclusion that Organizational Commitment mediates the influence of Job Satisfaction on Turnover Intention, the results discover that the Job Satisfaction has an indirect effect that is larger than the direct influence on Turnover Intention.